Hypermelanic and hypomelanic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
In literature there exists achromic nevus (nevus depigmentosus). A clinically identical but hyperpigmented lesion is usually called café-au-lait spot, sometimes with the addition of “innocent”. Hyperpigmented lesions distributed on the abdomen along the Blaschko lines are called linear and whorled nevoid hypermelanosis. Nevoid hypo-hyperpigmented lesions are recently called pigmentary mosaicism. This last term refers to a pathogenetic mechanism and could explain case 1, interpretable as a didymosis (2) by loss of heterozygosity of contiguous genes on two neighboring regions of the same chromosome. The term café-au-lait spot can create unnecessary worries for those who are used to consulting the web and the term pigmentary mosaicism is rather generic. If the term achromic nevus has reason to exist it would be preferable to speak about hypercromic or better hypermelanic nevus (1).